Islamic Republic of Mauritania : 2005 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Islamic Republic of Mauritania. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
Mauritania was one of the countries to reach the completion point under the enhanced Initiative for Heavily Indebted Poor Countries. The revised fiscal, balance of payments, and monetary data, including data on commercial banks, revealed that the main program parameters were missed by large margins. In 2003-04, progress in structural reforms was slower than planned, and major weaknesses surfaced in fiscal, monetary, and exchange rate management. Executive Directors welcomed the authorities' intention to gear medium-term spending plans toward poverty reduction.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet